Development of Islamic Education Teacher Through Reactualization of Objectives and Materials in Training Programs in Digital Age - Quraisy, Sherly; Fadli, Marsuki; Nurhadi, Ali (Maharot : Journal of Islamic Education, 2023)
Macro wise, there are many opinions that say Islamic education graduates do not prioritize aspects of development in the global era, such as mastery of technology. With the training by reactualizing the objectives and program materials in training, helping Islamic education teachers in technological developments in the global era. This paper discusses about the reactualization of educational program objectives and materials in Islamic education teacher training in the technological era.Â  By combining digital-based training objectives and materials. The method in this study uses qualitative library research that combines library data, then data in the field and notes related to the reactualization of objectives and material in training. The result of this article is to help Islamic education teachers on digital-based technology so that it can facilitate the teaching and learning process.